Penanaman Nilai Agama Dan Moral Aud Melalui Habituasi Sholat Dhuha di Ra Asyuhada’ - Pauzah, Pauzah; Ismaiyah, Nurul; laili, Faidatul; Robi'ah, Maulidatur; Rohelah, Mukhlisatur; Agustin, Maulidia (E-JURNAL AKSIOMA AL-ASAS, 2024)
Abstract Instilling religious and moral values ​​in early childhood is an important step in the formation of sustainable character. This period is a critical period because children easily absorb moral and religious values. One effective method is the routine of dhuha prayer,namely the habitual performance of the sunnah dhuha prayer in the PAUD educational environment. This method not only introduces children to worship, but also internalizes moral values ​​such as discipline, responsibility, perseverance, and calmness. The research method chooses a qualitative descriptive approach, Data collection techniques through observation and interviews and documentation. The results of the study showed that children who consistently perform dhuha prayers understand religious values ​​and demonstrate better moral behavior. The habituation of dhuha prayers is applied to form a generation with a solid and sustainable religious and moral foundation. Thus, the habituation of dhuha prayers is not only a physical habit, but also a means of strengthening the religious and moral character of early childhood holistically. Keywords: Cultivation of religious moral values of AUD, habituation, dhuha prayer